Design of radiation of the dipol electron-beam antenna - Lonin, Yu.F.; Ponоmarev, A.G.; Stolarchuk, A.V.; Zvyagintsev, A.Yu.; Chumakov, V.I. (Вопросы атомной науки и техники, 2011)
Actuality of problem of generation and radiation of ultra-wideband (UWB) signal makes experimenting with new
methods of excitation of the radiating systems. For forming of radiations of high intensity the high-currents accelerating
of electrons is used lately quite often. Theoretical and experimental researches show possibility of generation of
impulses with a relatively wide spectrum which is determined by variation of energy of electrons at the front front of
bunch. The results of design of dipole electronic beams of antenna (EBА) at excitation by the impulses of current of
different form are resulted in the real work. Актуальність проблеми генерування та випромінювання надширокосмугових (НШС) сигналів примушує
експериментувати з новими методами збудження випромінюючих систем. Для формування випромінювань
високої інтенсивності останнім часом застосовуються сильноточні прискорювачі електронів (СПЕ). Теоретичні
і експериментальні дослідження показують можливість генерування імпульсів з відносно широким спектром,
який визначається розкидом енергії електронів на передньому фронті пучка. У роботі приведено результати
моделювання діпольної електронно-пучкової антени при збудженні імпульсами струму різної форми. Актуальность проблемы генерирования и излучения сверхширокополосных (СШП) сигналов заставляет
экспериментировать с новыми методами возбуждения излучающих систем. Для формирования излучений
высокой интенсивности в последнее время нередко применяются сильноточные ускорители электронов (СУЭ).
Теоретические и экспериментальные исследования показывают возможность генерирования импульсов с
относительно широким спектром, который определяется разбросом энергии электронов на переднем фронте
пучка. В работе приведены результаты моделирования дипольной электронно-пучковой антенны при
возбуждении импульсами тока различной формы.